The Voltage Analysis of the Transmission Network in the Aceh Subsystem During the Energization of the 275 KV Nagan–Sigli Sutet using Digsilent - Pakpahan, Rosmeri Br; Anisah, Siti; Faisal, Ahmad (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
Voltage In Accordance With A Steady State. In 2023, The Aceh Subsystem Received An Additional 440 Mw Of Power Plants And In 2025 Will Be Energized Sutet Nagan - Sigli 275 Kv #1 Then With The Addition Of This Network There Will Be Changes In The Transmission Network. Based On The Problems Above, The Author Will Analyze The Impact That Occurs When The Conductor Enters. In This Final Project, A Simulation Is Carried Out With The Entry Of The Conductor And The Voltage Response In The Aceh Subsystem Using The Digsilent Power Factory 15.1 Application. So That The Location That Experiences High Voltage At The Main Substation Is Obtained, Both At Gi 150 Kv Or Gitet 275 Kv. The Simulation Results Show That When Energizing The Conductor Sutet Nagan - Sigli 275 Kv #1 Will Have An Impact On Overvoltage Voltage In Almost All Main Substations. In Overcoming This, It Is Highly Recommended To Install A Reactor At Gitet Sigli As A Node Substation To Improve The Voltage To Be Stable According To Pln Recommendations.